Characterisation and surface chemical modification of starch nanoparticles with lactid through ring opening polymerisation. (1st January 2014) - Fathi, Farzaneh; Dadkhah, Abbas; Namazi, Hassan
Waxy corn starch nanoparticles were prepared by an acid treatment process. The obtained starch nanoparticles were modified by ring opening polymerisation of lactide and the structure of the resulted polymers characterised with Fourier transform infrared (FTIR) spectroscopy. Weight fraction of starch nanoparticles and modified starch calculated by elemental analysis experiment. Thermal characteristic of the modified starch nanoparticles was investigated using thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC) techniques. By surface chemical modification of starch nanoparticles, the thermal properties of modified starch nanoparticles have improved and starch nanoparticles showed greater thermal stability. Also wettability tests showed that the surface characters of starch nanoparticles have been changed during modification and modified starch nanoparticles have higher affinity toward organic solvents rather than aqueous media. X-ray diffraction studies showed that the starch crystalline structure has not changed during the reaction.